RAD51 supports spontaneous non-homologous recombination in mammalian cells, but not the corresponding process induced by topoisomerase inhibitors - Arnaudeau, Catherine (Oxford University Press, 2001)
The RAD51 protein has been shown to participate in homologous recombination by promoting ATP-dependent homologous pairing and strand transfer reactions. In the present study, we have investigated the possible involvement of RAD51 in non-homologous recombination. We demonstrate that overexpression of CgRAD51 enhances the frequency of spontaneous non-homologous recombination in the hprt gene of Chinese hamster cells. However, the rate of non-homologous recombination induced by the topoisomerase inhibitors campothecin and etoposide was not altered by overexpression of RAD51. These results indicate that the RAD51 protein may perform a function in connection with spontaneous non-homologous recombination that is not essential to or not rate-limiting for non-homologous recombination induced by camptothecin or etoposide. We discuss the possibility that the role played by RAD51 in non-homologous recombination observed here may not be linked to non-homologous end-joining.